Sharing a polluted river through environmental taxes - María Gómez-Rúa (SERIEs - Journal of the Spanish Economic Association, 2013)
n agents located along a river generate residues that then require cleaning to return the river to its natural state, which entails some cost. We propose several rules to distribute the total pollutant-cleaning cost among all the agents. We provide axiomatic characterizations using properties based on water taxes. Moreover, we prove that one of the rules coincides with the weighted Shapley value of a game associated with the problem.
Keywords: C71; D61; 330; cost sharing; pollutant-cleaning cost; water taxes